Incivility and disrespectfulness in online political discussion - Angga Prawadika Aji; Ari Sapto (Masyarakat, Kebudayaan dan Politik, 2020)
Reader’s comment columns on online political news pages are locations where political discussions between citizens can emerge and develop. The reader comment column is a standard feature of almost all media sites because of its ability to initiate discussion and promote a particular article or issues within the news site. Unfortunately, in its development, the online comment column’s discussion process is often filled by incivility and disrespectful expressions, such as sentences containing insults, condemnation, or expressions full of anger. Such sentences have the potential to undermine the discussion process and encourage pointless arguments, especially in articles that discuss political polarity. This study aims to determine the extent to which incivility and disrespectful expressions appear in readers’ comments columns of online news sites, especially on polarized political issues. This study uses content analysis techniques on 403 comments in political news on Detik.com, one of Indonesia’s main news portals. The results show that although the incivility expression shows a small number, the form of disrespectful shows a high number in the readers’ comments. The highest form of the expression of disrespectful is the expression tat contains name-calling (23%), followed by hyperbole (15.6%) and the use of sarcasm (6.2%). The high number of disrespectful expressions seems to be related to the comment column service feature that allows users to use anonymous identities.